Human capital business partner information technology and network technology manpower model - A. Halim, Siti Sarah; Zeki, Akram M. (2011)
In view of the robust market situation whereby optimum manpower strength is very vital to meet the demand by the Line of Businesses (LOBs), Human Capital Business Partner Information Technology and Network Technology (HCBP ITNT) Manpower Model is required to have a proper tool to assist management in doing resource planning. This model is to decide on the effect of variables on the optimum level of manpower strength under given scenario to ascertain the optimum level of manpower strength under those situations. It shall be the one-stop information gateway and knowledge based exchanged for HCBP ITNT and the users to achieve.